Analisa Perbandingan Lelang Konvensional dengan Lelang Syariah pada Jaminan Rumah (Studi Kasus di KOSPIN GAMA Slawi & KSPPS BMT (KMA) Kanzul Mubarokah An – Nahdiyah Tegal - Titi Rahayu; Ahmad Faqih Udin; Khomsatun Yuliyani (Syntax Idea)
An auction is a form of public sale of goods conducted openly to the public, with bidding prices that increase or decrease to reach the highest price. Bids can be submitted in writing or orally, and they are preceded by prior notification of the upcoming auction. The auctions conducted by Kospin Gama and KSPPS BMT KMA take place at the Office of State Property and Auction Services (KPKNL) through a website. Prior to conducting the auction, Kospin Gama and KSPPS BMT KMA provide advance notice to debtors. If there is no ability to settle the debt, an auction is conducted. The purpose of this study is to understand how the auction process is carried out and to compare the auctions conducted by Kospin Gama and KSPPS BMT KMA. In this research, the researcher employs field research methodology using a qualitative approach. Data is collected through interviews and documentation in the form of sound recordings. The research findings conclude that there are several differences in the process of auctioning collateralized properties conducted by Kospin Gama and KSPPS BMT KMA: a) Mechanism of Auction Price Determination, b) Notification of Auction Information to Customers, c) Utilization of Excess Funds from Auction Proceeds